Trzy tezy o sędziach społecznych i ich udziale w sprawowaniu wymiaru sprawiedliwości w Polsce - Juchacz, Piotr W. (Uniwersytet im. A. Mickiewicza w Poznaniu Wydział Nauk Społecznych, Instytut Filozofii UAM, 2016)
In the article author states and justifies three theses on the lay judges and their participation in the exercise of justice in Poland. First thesis claims that the statement about the lack of integration in the community of lay judges in Poland is not true any longer and it is possible to observe the beginning of a process of its integration and cooperation connected with the recent establishment and activity of the Association National Council of Lay Judges. The second thesis states, that it is necessary to roaden the participation of citizens in the exercise of justice as a remedy for a low level of legitimacy and credibility of the judiciary. According to the third thesis Poland is presently in need of a widespread public debate concerning the reform of the institution of lay judges which should lead to a real fulfilment of the constitutional right of citizens to participate in the exercise of justice.
Three Theses on the Lay Judges and Their Participation in the Exercise of Justice in Poland
Keywords: lay judges; the participation of citizens in the exercise of justice; judiciary; the Association National Council of Lay Judges; the reform of the institution of lay judges